Old Urbanites as New Urbanists? Mixing at an Ancient Maya City. (July 2021) - Hutson, Scott R.; Welch, Jacob
New Urbanists advocate for, among other things, spaces in cities where people of various backgrounds can interact. Yet not all interactions lead to the strong social bonds that make diverse communities more durable. The archaeological record provides rich examples of diverse communities that flourished. This article examines an ancient Maya city—Chunchucmil—where preservation of stone walls and pathways provides an unusual opportunity to reconstruct urban design in great detail. Analysis of neighborhood circulation patterns shows that people of very different wealth levels shared space on a daily basis. We present evidence that Chunchucmil's diverse neighborhoods were also cohesive, and we identify a number of circumstances—worshipping together, working together, and maintaining local control over neighborhood affairs—that help interactions between different kinds of people develop into strong bonds. These circumstances are germane to contemporary contexts.